Applying Timor Leste Traditional Conflict Resolution on the Tigray War Conflict: Jaarsummaa and Qaalluu Method - Muhammad Abiel Dewa Pratama (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The Tigray War is an ongoing civil conflict that started on November 3, 2020, in Ethiopia's Tigray Region. The idea was first up in June 2005 by the International Criminal Court (ICC), which said that "normal procedures of conflict settlement may possibly meet the criteria for justice." By fusing well-established conflict settlement processes with local knowledge, this proclamation launches efforts by the international legal community to solve problems with peace and justice. On an international, regional, and national level, peace is said to be created by giving local people the tools they need to handle their own problems using conventional methods. This article examines the Gada system's Jaarsummaa and Qaalluu dispute resolution strategy, taking inspiration from Timor Leste traditional conflict resolution.